Investigation of Micromorphology and Carrier Recombination Dynamics for InGaN/GaN Multi-Quantum Dots Grown by Molecular Beam Epitaxy - Xue Zhang; Wenxian Yang; Zhiwei Xing; Haibing Qiu; Ying Gu; Lifeng Bian; Shulong Lu; Hua Qin; Yong Cai; Yuta Suzuki; Sakuya Kaneko; Yuki Matsuda; et al. (Crystals, 2021)
InGaN quantum dots (QDs) are promising candidates for GaN-based all-visible optoelectronic devices such as micro light-emitting diode and laser. In this study, self-assembled InGaN/GaN multi-quantum dots (MQDs) have been grown by plasma-assisted molecular beam epitaxy on c-plane GaN-on-sapphire template. A high density of over 3.8 × 1010 cm−2 is achieved and InGaN QDs exhibit a relatively uniform size distribution and good dispersity. Strong localization effect in as-grown InGaN QDs has been evidenced by temperature-dependent photoluminescence (PL). The variation of peak energy is as small as 35 meV with increasing temperature from 10 K to 300 K, implying excellent temperature stability of emission wavelength for InGaN MQDs. Moreover, the radiative and nonradiative recombination times were calculated by time-resolved PL (TRPL) measurements, and the temperature dependence of PL decay times reveal that radiative recombination dominates the recombination process due to the low dislocation density of QDs structure.